2014
DOI: 10.1080/09712119.2014.888003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin on cloacal temperature and erythrocyte osmotic fragility in layer hens during the hot-dry season

Abstract: Experiments were conducted with the aim of determining effects of melatonin on fluctuations in cloacal temperature (CT) and erythrocyte osmotic fragility (EOF) of layer hens. The CT of 14 melatonin-treated and 12 control laying hens were taken for 2 days, 1 week apart, at 06:00 h, 14:00 h and 18:00 h, using a standard digital thermometer inserted into the cloaca. The control birds were given water only, while the treated layers were individually administered at 18:00 h with melatonin orally. On day 12 of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
4
12
0
Order By: Relevance
“…The results of the present study show that heat stress induced significant haemolysis in broiler chickens. The findings of the present study also agree with those of Sinkalu et al (2015), who showed that high thermal environmental conditions in poultry housing adversely affect the EOF of broiler chickens during the hot-dry season in the zone. THI is an index of thermal comfort.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of the present study show that heat stress induced significant haemolysis in broiler chickens. The findings of the present study also agree with those of Sinkalu et al (2015), who showed that high thermal environmental conditions in poultry housing adversely affect the EOF of broiler chickens during the hot-dry season in the zone. THI is an index of thermal comfort.…”
Section: Discussionsupporting
confidence: 82%
“…Under such adverse conditions, the body is not able to synthesize the enzymes required to destroy ROS or repair the damage. The hot-dry season, characterized by high AT and high RH, in the Northern Guinea Savannah zone has been shown to be thermally stressful to poultry (Sinkalu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…CT was obtained (as a measure of core body temperature; Sinkalu, Ayo, Abimbola, et al 2014;Sinkalu, Ayo, Adelaiye, et al 2014) using a digital thermometer (Kruuse Incorporated, Denmark). The thermometer was inserted about 3 cm into the cloaca and tilted to make contact with the wall of the cloaca.…”
Section: Ct Measurementsmentioning
confidence: 99%
“…For this purpose, a digital clinical thermometer (Hartmann, Paul Hartman AG, Heidenheim, Germany), was inserted approximately 2 cm for the 21 st day and 5 cm for the 42 nd day into the cloaca and in direct contact with the mucosal wall. The value was recorded after the thermometer gave an alarm sound, indicating that the reading had been stabilized (Sinkalu et al, 2015). At the end of the experiment, 15 birds in each group were slaughtered humanly to get lymphoid organ (spleen, liver and bursa fabricius) weights…”
Section: The Effects Of Environmental Enrichment On Some Physiologicamentioning
confidence: 99%
“…of the fifteen birds from each group were measured at 06:00 h, 14:00, and 18:00 h of the 21 st and the 42 nd day by one observer because these hours refer to daily climate changes during the day (Sinkalu et al, 2015). For this purpose, a digital clinical thermometer (Hartmann, Paul Hartman AG, Heidenheim, Germany), was inserted approximately 2 cm for the 21 st day and 5 cm for the 42 nd day into the cloaca and in direct contact with the mucosal wall.…”
Section: The Effects Of Environmental Enrichment On Some Physiologicamentioning
confidence: 99%